Foreign policy and science: Switzerland actions to address the climate crisis effects in the arctic through the arctic council - Aristama, Ferga; Tobing, Fredy Buhama Lumban (Universitas Islam Malang, 2023)
like to have limited social-economy material advantage, Switzerland's action to actively and continuously participate in the Arctic Council is an interesting topic to discuss. Existing literature has captured Switzerland's actions to fight against the climate crisis, yet missed to address why it carried to participate in the Council amidst likely-limited materialistic returns. Deploying Foreign Policy Analysis and Resources Based Theory of Soft Power as an analytical approach and qualitative approach, this study argues that Switzerland's Foreign Policy which specifically emphasizes action in climate protection and global environment is the reason behind its active participation in various global communities, including in the Arctic Council. Interestingly, Switzerland utilizes science as an instrument of diplomacy and constructs its identity as a global science policy advisor in the environmental sector. Thus, the global climate crisis issues have been an opportunity for Switzerland as a small power to enhance its bargaining position in international politics through science as a soft power.